Effect of annealing temperature on morphology and physicochemical properties of cornstarch complexed with oleic acid and molecular dynamics simulation. Issue 4 (20th May 2019) - Zhang, Xing; Wang, Yu‐Sheng; Chen, Hai‐Hua
Abstract: Background and objectives: Annealing treatment (ANN) as a mild hydrothermal method to improve the complexation between starch and lipids has scarcely been studied. Moreover, the mechanism of starch pretreated by ANN on the complexation between starch and fatty acid still has not been investigated. Therefore, the object of this research was to investigate the effect of ANN pretreatment temperature (50, 55, and 60°C) on the morphology, crystal structure, and thermal properties of CSANN ‐OA complex by using confocal laser scanning microscope (CLSM), X‐ray diffraction (XRD), and DSC. The mechanism of the complexation between starch and OA was simulated by the molecular dynamics simulation (MDS) method. Findings: The results of complex indexes (CI) indicated that CSANN was easier to complex with OA than CSU, and the optimal ANN pretreatment temperature to promote the complexation between CSANN and OA was 50°C. The CLSM displayed that ANN pretreatment at 50°C caused more and stronger fluorescence fragments in CSANN ‐OA than that of ANN pretreatment at 55 or 60°C. XRD of both CSU ‐OA and CSANN ‐OA changed to V‐type crystalline. The relative crystallinity (RC) and gelatinization enthalpy (Δ H ) of the complex were decreased with increasing ANN pretreatment temperature, but the gelatinization temperature range ( T c – T o ) remains unchanged. According to results of MDS, Van der Waals might be dominate driving force between AM and OA. Conclusions: These results suggest that ANN pretreatment is an effective method to promote the complexation of ANN starch with more polar or nonpolar components. Significance and novelty: This result can provide available information about the complexation effect and complexation mechanism between starch subjected to ANN pretreatment and fatty acid.